Magnetic resonance spectroscopy in the rodent brain: Experts' consensus recommendations. (26th August 2020) - Lanz, Bernard; Abaei, Alireza; Braissant, Olivier; Choi, In‐Young; Cudalbu, Cristina; Henry, Pierre‐Gilles; Gruetter, Rolf; Kara, Firat; Kantarci, Kejal; Lee, Phil; Lutz, Norbert W.; Marjańska, Małgorzata; et al.
Abstract : In vivo MRS is a non‐invasive measurement technique used not only in humans, but also in animal models using high‐field magnets. MRS enables the measurement of metabolite concentrations as well as metabolic rates and their modifications in healthy animals and disease models. Such data open the way to a deeper understanding of the underlying biochemistry, related disturbances and mechanisms taking place during or prior to symptoms and tissue changes. In this work, we focus on the main preclinical 1 H, 31 P and 13 C MRS approaches to study brain metabolism in rodent models, with the aim of providing general experts' consensus recommendations (animal models, anesthesia, data acquisition protocols). An overview of the main practical differences in preclinical compared with clinical MRS studies is presented, as well as the additional biochemical information that can be obtained in animal models in terms of metabolite concentrations and metabolic flux measurements. The properties of high‐field preclinical MRS and the technical limitations are also described. Abstract : We present here the main preclinical 1 H, 31 P and 13 C MRS approaches to study brain metabolism in rodent models, with the aim of providing general experts' consensus recommendations (animal models, anesthesia, data acquisition protocols). An overview of the main practical differences in preclinical compared with clinical MRS studies as well as the additional biochemical information is presented, and the technical limitations are also described.